2022
DOI: 10.3390/jcm11144067
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on Subclinical Placental Thrombosis and Maternal Thrombotic Factors

Abstract: Background: In the context of the SARS-CoV-2 pandemic, our interest was to evaluate the effect of COVID-19 during pregnancy on placenta and coagulation factors. Methods: a prospective cohort study between January and July 2021 of 55 pregnant women stratified into: Group O, 16 patients with ongoing SARS-CoV-2 infection at delivery; Group R, 21 patients with a history of SARS-CoV-2 infection during pregnancy but who recovered prior to delivery; Group C, 18 control patients with no infection at any time. All wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 39 publications
(57 reference statements)
0
1
0
Order By: Relevance
“…The systematic literature review identified 38 studies with n=3677 placentas meeting the inclusion criteria 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 ( Table 1 ). Concerning the size of placentas, 20% of cases were too small for gestational age (< 10 th percentile) and 6% of COVID-19-associated placentas were too large (> 90 th percentile).…”
Section: General Findings In Placentas Of Covid19-pregnanciesmentioning
confidence: 99%
“…The systematic literature review identified 38 studies with n=3677 placentas meeting the inclusion criteria 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 ( Table 1 ). Concerning the size of placentas, 20% of cases were too small for gestational age (< 10 th percentile) and 6% of COVID-19-associated placentas were too large (> 90 th percentile).…”
Section: General Findings In Placentas Of Covid19-pregnanciesmentioning
confidence: 99%